Temporally uncoupled signal and coding joint formation in human V(D)J recombination. (December 2020) - Hsieh, Chih-Lin; Okitsu, Cindy Y.; Lieber, Michael R.
Highlights: The cellular efficiency of signal relative to coding end joining in V(D)J recombination is not known. ddPCR permits independent analysis of signal (SJ) and coding joints (CJ) on inversion substrates. SJ and CJ formation are temporally uncoupled such that one joint can often remain incomplete when the other has formed. Despite their temporal gap, the overall ratio of SJ/CJ is close to 1 in a human pre-B cell line. Abstract: In vertebrate antigen receptor gene rearrangement, V(D)J recombination events can occur by deletion or by inversion. For deletional events, the signal joint is deleted from the genome. Nearly half of the immunoglobulin light chain genes undergo V(D)J recombination in an inversional manner, and both signal and coding joint formation must occur to retain chromosomal integrity. But given the undetermined amount of pre-B and pre-T cell death that occurs during V(D)J recombination, the efficiency with which both joints are completed is not known, nor is the relative efficiency (balance) of signal versus coding joint formation. Signal joint formation only requires Ku and XRCC4:DNA ligase 4 of the nonhomologous DNA end joining repair pathway. Coding joint formation requires these proteins as well, but in addition requires Artemis and DNA-dependent protein kinase to open the hairpin DNA coding ends, which the RAG complex generated; and further processing is required because the hairpin opening generates incompatible 3′ overhangs. Mutations in some of the end processing enzymes affect one, but only minimally the other joint. We have devised a precise cellular assay that does not have any cellular, enzymatic or biochemical selective bias to assess signal and coding joint formation independently, and it can detect intermediates for which one joint has formed but not the other. We find that intermediates with only one completed joint are more abundant than molecules with both joints completed. This indicates that either joint can form independent of the other and joint formation can be a relatively slow process.